2009
DOI: 10.1901/jeab.2009.91-213
|View full text |Cite
|
Sign up to set email alerts
|

Isolating Behavioral Mechanisms of Intertemporal Choice: Nicotine Effect on Delay Discounting and Amount Sensitivity

Abstract: Many drugs of abuse produce changes in impulsive choice, that is, choice for a smaller-sooner reinforcer over a larger-later reinforcer. Because the alternatives differ in both delay and amount, it is not clear whether these drug effects are due to the differences in reinforcer delay or amount. To isolate the effects of delay, we used a titrating delay procedure. In phase 1, 9 rats made discrete choices between variable delays (1 or 19 s, equal probability of each) and a delay to a single food pellet. The comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
46
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(50 citation statements)
references
References 24 publications
4
46
0
Order By: Relevance
“…If both life-course-persistent and adolescence-limited deviancy are a result of the decreased effectiveness of delayed rewards at controlling behavior in each group, a differing etiology of risk between the two groups may indicate that the mechanism underlying rapid discounting in each group also differs. The potential for multiple mechanisms controlling the rate of discounting is consistent with the multiple processes shown to contribute to discounting: working memory (Bobova et al, 2009); timing (Galtress et al, 2012); reward sensitivity (Locey & Dallery, 2009); as well as distinct brain regions/neurotransmitter systems (MacKillop, 2013; Monterosso et al, 2007; Stanger et al, 2013). Animal models of the rapid discounting seen in life-course-persistent and adolescence-limited deviancy might help us to discover the mechanisms underlying the rapid discounting seen in each group; and thus, aid in developing ways of ameliorating the consequences of this rapid discounting in each group, and in particular mouse models might be especially useful given the powerful tools for studying genetic factors in mice.…”
Section: 0 Delay Discounting and Choicesupporting
confidence: 57%
“…If both life-course-persistent and adolescence-limited deviancy are a result of the decreased effectiveness of delayed rewards at controlling behavior in each group, a differing etiology of risk between the two groups may indicate that the mechanism underlying rapid discounting in each group also differs. The potential for multiple mechanisms controlling the rate of discounting is consistent with the multiple processes shown to contribute to discounting: working memory (Bobova et al, 2009); timing (Galtress et al, 2012); reward sensitivity (Locey & Dallery, 2009); as well as distinct brain regions/neurotransmitter systems (MacKillop, 2013; Monterosso et al, 2007; Stanger et al, 2013). Animal models of the rapid discounting seen in life-course-persistent and adolescence-limited deviancy might help us to discover the mechanisms underlying the rapid discounting seen in each group; and thus, aid in developing ways of ameliorating the consequences of this rapid discounting in each group, and in particular mouse models might be especially useful given the powerful tools for studying genetic factors in mice.…”
Section: 0 Delay Discounting and Choicesupporting
confidence: 57%
“…1), and q is a fitted parameter that moderates the effects of Q , reward quality, which contributes to the incentive value of the reward. A slightly different approach is taken by Locey & Dallery (2009), in which a sensitivity exponent ( z ) is added to A to modulate an individual’s response to both reward amount and delay in combination: V=Az11+kD…”
Section: Description Of Other Quantification Proceduresmentioning
confidence: 99%
“…Several studies using non-human subjects have shown that exposure to some drugs result in an increase in delay discounting (e.g., methamphetamine and nicotine with rats (89,90), cf. (91), although such effects can differ depending on the drug, drug dose, procedure, and testing conditions. Other studies using rats have shown that pre-drug discounting rates can be used to predict various aspects of drug taking and relapse to drug use (86,92,93).…”
Section: Variables That Influence the Effects Of CM On Abstinencementioning
confidence: 99%